Comparative analysis of Penicillium genomes reveals the absence of a specific genetic basis for biocontrol in Penicillium rubens strain 212 - Requena, Elena; Alonso-Guirado, Lola; Veloso, Javier; Villarino, María; Melgarejo, Paloma; Espeso, Eduardo Antonio; Larena, Inmaculada (Frontiers in Microbiology, 2023)
Penicillium rubens strain 212 is a filamentous fungus belonging to division Ascomycete. PO212 acts an effective biocontrol agent (BCA) against several pathogens in a variety of horticultural crops including Fusarium oxysporum f.sp. lycopersici, causing the vascular wilt disease in tomato plants. This is the first Penicillium strain with biocontrol activity whose genome has been sequenced and compared. PO212 genome size is 29,82Mb currently organized into 65 scaffolds and with a prediction of 10,164 ORFs. Sequencing has confirmed that PO212 belongs to P. rubens clade. Comparison with other P. rubens and P. chrysogenum genomes available in databases has made possible to assess this genome among those of the same species but made it difficult to stablish a connection between genomic data and biocontrol phenotype. Thus, sequencing of a non-biocontrol P. rubens strain S27 was done finding high sequence conservation and a low number of variations specially in ORF regions. These differences in coding regions between PO212 and S27 genomes cannot explain the biocontrol activity of PO212 or the absence of such activity in S27 strain, leaving the door open for transcriptomic and epigenetic studies that may shed light on this mechanism for fighting plant diseases caused by fungal pathogens. The genome sequences described here provide a useful novel resource for future research into the biology, ecology and evolution of BCA.